NiFe layered double hydroxide nanosheet arrays for efficient oxygen evolution reaction in alkaline media - Huang, Feng (2022)
Exploring efficient oxygen evolution reaction (OER) catalysts synthesized from low-cost and earth-abundant elements are crucial to the progression of water splitting. In this paper, NiFe layered double hydroxide (LDH) nanosheets were grown on Ni foam (NF) through a straightforward hydrothermal method. The Fe doping effects were systematically investigated by controlling Ni/Fe ratios and Fe valence states, and the in-depth influence mechanisms were discussed. The results indicate that, through controlling structure morphology and enhancing Ni2+ oxidation, NiFeIII(1:1)-LDH displays the best and outstanding OER performance, with a low over potential of 382 mV at 50 mA cm−2, a low Tafel slope of 31.1 mVdec−1 and only 20 mV increase after 10 h continuous test at 50 mA cm−2. To our knowledge, this is one of the best OER electrocatalysts in alkaline media to date. This work provides a facile and novel strategy for the fabrication of bimetallic LDH catalysts with desired structures and compositions.